The genus Megacraspedus Zeller, 1839 in Portugal with description of four new species (Lepidoptera: Gelechiidae) - Martin F. V. Corley; Sónia Ferreira (SHILAP)
Huemer & Karsholt (2018) presented a comprehensive revision of the Palaearctic genus Megacraspedus Zeller, 1839, recognising four species as present in Portugal. Prior to this Corley (2015) included only two species of the genus in the Portuguese list, but neither of these species is given for Portugal by Huemer & Karsholt (2018). In this paper these differences are reconciled and four new species (M. dalei Corley, sp. nov., M. transmontanus Corley, sp. nov., M. dinensis Corley, sp. nov., and M. terryae Corley, sp. nov.) are described, that were not included in Huemer & Karsholt (2018); we also add additional DNA barcode data and female genitalia illustrations that were not available in their revision. The four new Megacraspedus species, together with one newly added to the country and four species from validated bibliographic records, bring the total of Portuguese Megacraspedus species to nine.